Health services for cancer survivors practice, policy and research - Feuerstein, Michael; Ganz, Patricia; SpringerLink (Online service). (New York London Springer, 2011)
Health Services for Cancer Survivors Practice, Policy, and Research Michael Feuerstein and Patricia A. Ganz, editors Between early detection and current medical advances, more cancer patients are living longer post-treatment. But all too often, survivors? lives are complicated by medical, psychosocial, and economic challenges that their providers downplay as the ?new normal.? Health Services for Cancer Survivors replaces this scenario with an integrative, evidence-based framework for improving the health of survivors over the long term, across clinical settings and specific diagnoses. Emphasizing an interdisciplinary team approach, contributors review the current state of survivor care and model a proactive future. Human factors, particularly in the areas of symptoms and symptom reporting, health costs, and individualized care, are highlighted as keys to survivors? health, well-being, and functioning. The book offers diverse perspectives, informative data, and real-world case studies as it: Defines quality health care in the context of cancer survivor experience. Introduces the Cancer Survivorship Care Plan, a first-steps strategy for integrating survivor care. Pinpoints specific areas for improvement, including symptom management, health behaviors, rehabilitation, psychological well-being, and disparities in health care access and delivery.  Outlines practical strategies for optimizing primary, oncological, palliative community-based, and end-of-life care. Provides detailed information on epidemiology, health economics, and other areas critical to clinical decision-making. Analyzes the new health care reform measures as an opportunity to reform survivor care. Health Services for Cancer Survivors is essential, stimulating reading for a wide range of practitioners, including primary care physicians, health psychologists, social workers, nurses, physical and occupational therapists, and public health professionals.
Part 1. Current Concerns -- Specific challenges in optimizing the health care of survivors -- Providers? and cancer survivors? concerns about health care -- Epidemiology of recurrent and new cancers -- Symptoms over time: What is their role in surveillance?- Access to care among cancer survivors -- Symptoms among cancer survivors: Biobehavioral mechanisms and current health care response -- Part 2. Clinical Management -- General health -- Targeting provider-survivor communication -- Oncologic health -- Health behaviors: General strategies (diet, weight loss, exercise, stress) -- Behavioral health -- Functional outcomes -- Self-management -- The cancer survivorship clinic -- The cancer survivorship plan -- Part 3. Current Needs and Future Directions -- What works, and what should be stepped up?- Future challenges and potential solutions.
Electronic reproduction.
Keywords: Cancer -- Patients -- Services for; Cancer -- Patients -- Services for -- Government policy; Electronic books